Scour at marine structures a manual for practical applications - Whitehouse, Richard (Thomas Telford, 1998)
Brings together research results and practical findings to provide practitioners and researchers with a state-of-the-art review of scour by waves and currents, and provides methodology to assess the extent of scour at sites.